2016
DOI: 10.1037/emo0000228
|View full text |Cite
|
Sign up to set email alerts
|

Are empathy and concern psychologically distinct?

Abstract: Researchers have long been interested in the relationship between feeling what you believe others feel-often described as empathy-and caring about the welfare of others-often described as compassion or concern. Many propose that empathy is a prerequisite for concern and is therefore the ultimate motivator of prosocial actions. To assess this hypothesis, the authors developed the Empathy Index, which consists of 2 novel scales, and explored their relationship to a measure of concern as well as to measures of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
195
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(209 citation statements)
references
References 35 publications
10
195
1
3
Order By: Relevance
“…We focused on EC subscale based on prior work showing that higher EC is associated with more severe assessment of accidental harms 27,29 . In Study 2, we replicated this effect using another measure of trait empathy (Empathy index 43 ) and found a positive association between higher self-report scores of empathy and condemnation of accidents (r = 0.133, 95% CI [0.072, 0.193], t(1002) = 4.234, p < 0.001). In Study 3, we borrowed a recently developed measure designed to dissociate empathy from compassion 30 In summary, these studies supported the empathic blame hypothesis: individuals that either self-reported to have more empathic predisposition or reported to have stronger situational empathic engagement gave more Scientific RepoRts | 7: 5200 | DOI:10.1038/s41598-017-05299-9…”
Section: Studies (1-4): Empathy Predicts the Condemnation Of Accidentssupporting
confidence: 58%
“…We focused on EC subscale based on prior work showing that higher EC is associated with more severe assessment of accidental harms 27,29 . In Study 2, we replicated this effect using another measure of trait empathy (Empathy index 43 ) and found a positive association between higher self-report scores of empathy and condemnation of accidents (r = 0.133, 95% CI [0.072, 0.193], t(1002) = 4.234, p < 0.001). In Study 3, we borrowed a recently developed measure designed to dissociate empathy from compassion 30 In summary, these studies supported the empathic blame hypothesis: individuals that either self-reported to have more empathic predisposition or reported to have stronger situational empathic engagement gave more Scientific RepoRts | 7: 5200 | DOI:10.1038/s41598-017-05299-9…”
Section: Studies (1-4): Empathy Predicts the Condemnation Of Accidentssupporting
confidence: 58%
“…This differentiates it from empathy, which always involves sharing another's emotional state but does not always result in concern for that other (Eisenberg, Spinrad, & Knafo, 2015). As pointed out by several scholars (e.g., Eisenberg et al, 2014;Jordan, Dorsa, & Bloom, 2016), sympathy, in comparison to empathy, is likely to be more strongly associated with prosocial and aggressive behaviors across development. The mere vicarious experience of another's emotional state (i.e., empathy) "may be too remote from the behavior to predict it" (Vachon, Lynam, & Johnson, 2014, p. 766) and may result in aversive, personally distressing emotional reactions that often impede otheroriented behaviors (Eisenberg et al, 2014).…”
Section: Co-development Of Sympathy and Aggressionmentioning
confidence: 99%
“…Others have suggested that more reliable foundations are anger (Prinz, 2011) and compassion (Bloom, 2016(Bloom, , 2017aJordan et al, 2016;Klimecki et al, 2014). Yet anger and compassion can be impacted by the same factors that influence empathy: for instance, people are less likely to punish transgressors who harm more victims (Nordgren & McDonnell, 2011).…”
Section: Ends Of Empathy 49mentioning
confidence: 99%